Effects of aqueous and ethanolic extracts of Aegle marmelos (BAEL) leaves on chronic inflammation in rats - Rahman, Sharmin; Eva, Eliza Omar; Quader, Rezaul; Tasrin, Muqbula; Khan, Md Ismail (Ibrahim Medical College Journal, 2016)
Aegle Marmelos Linn (Rutaceae) is used as ethno medicine against various human ailments. Several curde extracts from various parts (Leaves, flower, stem, root etc) of the plant A. marmelos Linn have shown variable anti-inflammatory effects in acute and chronic inflammation in animal models. The anti-inflammatory effects of A marmelos linn may be of special advantage compared to conventional anti-inflammatory drugs. The present study has therefore been undertaken with the objective to evaluate the anti inflammatory effect of aqueous and ethanolic extracts of A. marmelos leaves, compared to a standard anti-inflammatory drug (indomethacin) in chronic inflammatory conditions. The anti-inflammatory effect was studied in rats using cotton pellet implantation, where granuloma formation was used as an index of chronic inflammation. Aqueous and ethanolic extracts of A. marmelos leaves were given orally for 7 days daily at doses of 100 mg/kg body weight. The percent inhibition of granuloma formation following treatment with aqueous and ethanolic extracts of A. marmelos leaves, and indomethacin compared to control were 16.5%, 25.72%, and 39.37% respectively. The differences were statistically significant (p<0.05 in case of aqueous and ethanolic extracts and p<0.001 in case of indomethacin). The results suggest that in case of chronic inflammation, both aqueous and ethanolic extracts of A. marmelos have significant anti- inflammatory effect. The ethanolic extracts compared to aqueous extract produced greater anti- inflammatory effects. Ibrahim Med. Coll. J. 2015; 9(2): 52-54